2001
DOI: 10.1177/00187267015411001
|View full text |Cite
|
Sign up to set email alerts
|

When Workers Flout Convention: A Study of Workplace Incivility

Abstract: Many organizations are concerned about the potential for workplace aggression and violence, yet pay little heed to lesser forms of interpersonal and organizational mistreatment. Drawing from knowledge and experiences of managers, attorneys, law enforcement officers and emergency medical professionals, we report a multi-method, multidisciplinary inductive study addressing two questions: (1) what is the nature of workplace incivility and how does incivility differ from and fit among other types of workplace mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
403
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(444 citation statements)
references
References 56 publications
11
403
0
14
Order By: Relevance
“…This and other research suggests that such oversight can carry substantial costs, potentially fostering employee distraction and discontentment, job accidents, overuse of sick leave, work team conflict, productivity decline, and turnover (Cortina et al, 2002;Pearson et al, 2000Pearson et al, , 2001. Such outcomes appear to extend beyond direct targets of uncivil conduct.…”
Section: Practical Implicationsmentioning
confidence: 90%
See 3 more Smart Citations
“…This and other research suggests that such oversight can carry substantial costs, potentially fostering employee distraction and discontentment, job accidents, overuse of sick leave, work team conflict, productivity decline, and turnover (Cortina et al, 2002;Pearson et al, 2000Pearson et al, , 2001. Such outcomes appear to extend beyond direct targets of uncivil conduct.…”
Section: Practical Implicationsmentioning
confidence: 90%
“…We thus see job satisfaction as a key mediator of the process by which incivility drives an employee out of an organization. Supporting these arguments, Pearson and colleagues (Pearson, Andersson, & Porath, 2000;Pearson, Andersson, & Wegner, 2001) found that targets of incivility often experienced negative affective and cognitive reactions at work (e.g., worrying about future interactions with the instigator), and many eventually quit their jobs. Initial data from Cortina et al (2001Cortina et al ( , 2002 also showed direct links between incivility experiences and lower job satisfaction.…”
Section: Work Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy in the treatments of intentionality in workplace crimes makes various types of crime hard to compare. For example, it is difficult to ascertain how crimes in the accounting industry (e.g., fraudulent financial statements) are related to employees' antisocial behaviors, such as organizational retaliatory behaviors (Skarlicki and Folger 1997) and workplace incivility (Pearson et al 2001).…”
Section: Typology Of Workplace Crimesmentioning
confidence: 99%